2020
DOI: 10.3390/jcm9103149
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Relationship between Telangiectasia and Cone Mosaic Disruption in Macular Telangiectasia Type 2

Abstract: In this cross-sectional observational study, we investigated the relationship between photoreceptor layer disruption and telangiectasia in patients diagnosed with early stage macular telangiectasia type 2 (MacTel). A total of 31 eyes (17 patients) with MacTel were imaged with adaptive optics scanning laser ophthalmoscopy (AOSLO) and optical coherence tomography angiography (OCTA). Confocal AOSLO was used to visualize dark regions of nonwaveguiding outer segments, which we refer to as “photoreceptor lesions”. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…These results are consistent with an overall model of IZ disruption occurring in the early stages, which then progresses to combined IZ and EZ changes in the later stages (Tables 2 and 3 and Fig 3). Our results are also consistent with qualitative data from previous small studies of MacTel eyes from our group and others, which found that areas of IZ disruption colocalize with hyporeflective lesions on AOSLO in zones where the EZ is still intact [27,29].…”
Section: Plos Onesupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with an overall model of IZ disruption occurring in the early stages, which then progresses to combined IZ and EZ changes in the later stages (Tables 2 and 3 and Fig 3). Our results are also consistent with qualitative data from previous small studies of MacTel eyes from our group and others, which found that areas of IZ disruption colocalize with hyporeflective lesions on AOSLO in zones where the EZ is still intact [27,29].…”
Section: Plos Onesupporting
confidence: 92%
“…The current neurodegenerative model of MacTel would suggest that vascular changes are secondary to underlying photoreceptor dysfunction [3,40]. These isolated telangiectatic areas may represent an earlier, "pre-IZ" stage of photoreceptor dysfunction that cannot be assessed on SD-OCT but may be visualized on imaging modalities like AOSLO [29]. Additionally, while both SD-OCT and AOSLO ultimately assess structural integrity of the photoreceptors, functional disruption will most likely precede observable structural damage.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Our group has previously shown an intricate and complex relationship between outer retinal telangiectasias and photoreceptor loss with progression of MacTel. 57 , 58 As MacTel progresses, the photoreceptors degenerate, with retinal thinning in those areas. 56 , 59 DCP telangiectasias and subsequent retinal deformation in areas of local photoreceptor loss and outer retinal degeneration may contribute to the appearance of outer retinal vascular abnormalities in MacTel.…”
Section: Discussionmentioning
confidence: 99%